1997
DOI: 10.1007/bf01676579
|View full text |Cite
|
Sign up to set email alerts
|

The effects of simple trauma on patients with cervical spine neurofibromatosis: Two case reports

Abstract: Von Recklinghausen's disease of the cervical spine is rare. Spinal deformities appear to occur only in peripheral neurofibromatosis as opposed to central neurofibromatosis, and such deformities include non-dystrophic and dystrophic changes. We describe two patients with neurofibromatosis of the cervical spine who were subjects of simple trauma, one of whom demonstrated dystrophic and the other nondystrophic changes. The first presented with acute upper cervical spine instability and subluxation, the second wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 3 publications
0
5
0
Order By: Relevance
“…Reported cases of NF-1 with spinal cord injury caused by minor trauma are summarized in Table 1 . 3 , 6 , 10 , 11) Despite a meticulous review of the literature, only seven cases, including the present case, were found. Considering the expected incidence of NF-1 with spinal deformity, this small number is said to be incredible.…”
Section: Discussionmentioning
confidence: 70%
See 4 more Smart Citations
“…Reported cases of NF-1 with spinal cord injury caused by minor trauma are summarized in Table 1 . 3 , 6 , 10 , 11) Despite a meticulous review of the literature, only seven cases, including the present case, were found. Considering the expected incidence of NF-1 with spinal deformity, this small number is said to be incredible.…”
Section: Discussionmentioning
confidence: 70%
“…Spinal deformity is the most commonly observed, but its incidence was reportedly ranged from 2% to 69% of NF-1 patients. 1 , 3 , 5) Akbarnia et al 1) believe that 10% is representative of the true prevalence of spinal deformity. Recent studies using MRI suggested a much higher incidence.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations